PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERDIFERENSIASI BERBASIS ANDROID - Purwanto, Ageng Jelly; Gita, Rina Sugiarti Dwi (Universitas Insan Budi Utomo, 2023)
Learning in the Kurikulum Merdeka is more focused on differentiated learning. There are three differentiated learning strategies, namely, content differentiation, process differentiation, and product differentiation. Learning in the Kurikulum Merdeka other than differentiation can also be supported by information technology. As technology develops, android application developers create android based learning media which are then distributed through the google play store. However, none of them are in accordance with differentiated learning so it is necessary to develop an application that suits the needs of students and is in line with the Kurikulum Merdeka. The learning media development design used is the ADDIE model with 5 stages, namely Analysis, Design, Development, Implementation, Evaluation and produces products in the form of android-based differentiated mathematics learning media which contains material, comics, games, calculators and practice questions. The material used is single interest and compound interest (exponential on number elements) in accordance with the learning outcomes in phase E of the Kurikulum Merdeka. Based on implementation results, students feel comfortable with the application because user friendly